Parallel front propagation in medical image segmentation - Yeghiazaryan, V (2017)
Newly emerging medical image modalities, large high-dimensional images with resolution and quality improved over time, introduce new challenges for traditionally sequential segmentation procedures. We contribute to three aspects of medical image segmentation, and we provide a new, more reliable way to evaluate the results of segmentation.